1991
DOI: 10.1111/j.1365-2133.1991.tb04952.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of involved surface area in patients with psoriasis

Abstract: Three methods of measuring the surface area of the involved skin were compared in 10 patients with psoriasis. Using the rule of nines, four untrained observers estimated the average extent of psoriasis as 20, 14, 23 and 33% of the body surface area. Measuring the area of tracings of plaque outlines using image analysis gave a mean involved surface area of 9% and image analysis of whole body photographs gave a mean value of 7%. We conclude that untrained observers using the rule of nines will overestimate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 6 publications
5
143
0
1
Order By: Relevance
“…Intra-rater reliability for the BSA has also previously been described as very good. 14,15 Two studies conducted by Berth-Jones et al have demonstrated substantial intra-rater reliability for the PASI and PGA, and higher reproducibility for the PASI than for the PGA. 8,12 However, the data presented by Langley and Ellis revealed over 12 times higher intrarater variation for the PASI than for the PGA.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-rater reliability for the BSA has also previously been described as very good. 14,15 Two studies conducted by Berth-Jones et al have demonstrated substantial intra-rater reliability for the PASI and PGA, and higher reproducibility for the PASI than for the PGA. 8,12 However, the data presented by Langley and Ellis revealed over 12 times higher intrarater variation for the PASI than for the PGA.…”
Section: Discussionmentioning
confidence: 99%
“…The rule of 9's, a method of estimating surface area based on attributing a given percentage to each body part, is used to estimate involved body surface area, e.g. in psoriasis (Ramsay, et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Other scores like Psoriasis Area and Severity Index (PASI) or SCORAD (SCORing Atopic Dermatitis) depend heavily on assessment of the skin area, but this assessment has repeatedly been shown to be hard to reproduce (Charman, et al, 2000;Tiling-Grosse, et al, 1993;Charman, et al, 1999). Because CLE, like guttate psoriasis, involves only small proportions of the skin, area assessment is even more difficult than in atopic dermatitis or plaque psoriasis (Ramsay, et al, 1991). Lesion counting, commonly used for acne, is not a suitable alternative, because the reliability of the lesion counting is not necessarily better (Lucky, et al, 1996) and the lesions of CLE have widely varying size and may be confluent.…”
Section: Areamentioning
confidence: 99%
“…Score <4 was considered as remission, in the range of >4 -<14 low disease activity, >14 -<28 moderate disease activity; whereas > 28 reflect high disease activity. Skin affection was assessed using both they included Body Surface Area (BSA) [18], and Psoriasis Area and Severity Index (PASI) [19]. PASI score <1 was considered in remission, score < 10 was considered as mild, 10-20 moderate whereas PASI score > 20 was considered as severe.…”
Section: Data Collectionmentioning
confidence: 99%